2017
DOI: 10.3390/su9081461
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield, Dry Weight and Phosphorus Accumulation and Translocation in Two Rice (Oryza sativa L.) Varieties as Affected by Salt-Alkali and Phosphorus

Abstract: Salt-alkali is the main threat to global crop production. The functioning of phosphorus (P) in alleviating damage to crops from saline-alkaline stress may be dependent on the variety of crop but there is little published research on the topic. This pot experiment was conducted to study if P has any effect on rice (Oryza sativa L.) yield, dry matter and P accumulation and translocation in salt-alkaline soils. Plant dry weight and P content at heading and harvest stages of two contrasting saline-alkaline toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…This indicated that P was at least in part being remobilized from shoot to grain as the plant underwent reproductive development. Thus, as noted by several authors, P remobilized from vegetative organs to the grain could account for about 25-30% of the grain P (Tiryakioǧlu et al 2014;Tian et al 2017;Xie et al 2018). The remaining grain P is taken up during the reproductive phase.…”
Section: Impact Of P On Crop Growth Yield and Nutritional Qualitymentioning
confidence: 73%
“…This indicated that P was at least in part being remobilized from shoot to grain as the plant underwent reproductive development. Thus, as noted by several authors, P remobilized from vegetative organs to the grain could account for about 25-30% of the grain P (Tiryakioǧlu et al 2014;Tian et al 2017;Xie et al 2018). The remaining grain P is taken up during the reproductive phase.…”
Section: Impact Of P On Crop Growth Yield and Nutritional Qualitymentioning
confidence: 73%
“…In terms of the HTLR, the HTLR under full-feeding and semi-feeding combine harvesting methods tended to increase with the extension of the harvest date. Since the whole field rice spikes appeared to sag gradually with the maturity of rice, the collision and friction between the spikes and the cutting platform could be more intense [37]. Thus, the falling grains increased under the external force, and the HTLR increased significantly [38].…”
Section: Discussionmentioning
confidence: 99%
“…This assessment was made during the mature stage (Tian et al, 2017), which is approximately 100 days after planting for both inflow and outflow regions. A non-saline paddy plot was chosen to observe the paddy growth as a comparison.…”
Section: Paddy Growth Assessment: Height and Yieldmentioning
confidence: 99%